2002
DOI: 10.1016/s0895-7061(02)02976-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of waist circumference to blood pressure: the Olivetti heart study1

Abstract: In middle-aged men, a central distribution of body fat is associated with increased BP, independently of body mass index and insulin resistance, thus suggesting a key role of central adiposity in the full expression of the "metabolic syndrome."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
53
3
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 28 publications
11
53
3
6
Order By: Relevance
“…Our findings show that men with abdominal obesity on its own had higher odds of hypertension than those without abdominal obesity (or BMI $ 30 kg m 22 ). The Olivetti Heart Study also showed that WC in men was a strong predictor of elevated blood pressure, independent of BMI and insulin resistance 27 .…”
Section: Discussionmentioning
confidence: 94%
“…Our findings show that men with abdominal obesity on its own had higher odds of hypertension than those without abdominal obesity (or BMI $ 30 kg m 22 ). The Olivetti Heart Study also showed that WC in men was a strong predictor of elevated blood pressure, independent of BMI and insulin resistance 27 .…”
Section: Discussionmentioning
confidence: 94%
“…Body composition in older adults KA Shaw et al with prevalent diabetes 16 and cardiovascular risk factors. 17,18 It may be that waist circumference is a better measure in older adults than WHR. In order to fully understand the usefulness of waist circumference in older adults, its ability to predict disease risk should be evaluated against that of WHR and other measures in longitudinal studies of older people.…”
Section: Discussionmentioning
confidence: 99%
“…These associations were independent of age, socioeconomic status and other major risk factors for hypertension. Numerous epidemiologic studies [1][2][3][4][5][6]12,13,[21][22][23][24] and interventional trials [25][26][27][28] have demonstrated that weight change and excess weight plays a major role in determining BP levels, particularly among individuals with high BP. Few studies have evaluated the impact of weight and weight change on BP in normotensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Body fat distribution has also been shown to contribute to the genesis of obesity-hypertension syndrome. [4][5][6] Previous studies that have addressed these issues focused primarily on hypertension [7][8][9][10][11] and largely involved populations with a high prevalence of overweight and obesity. [8][9][10]12 Few studies have evaluated the impact of weight change, attained body weight and fat distribution on BP among individuals with normal BP, [12][13][14] particularly those who are relatively lean.…”
Section: Introductionmentioning
confidence: 99%